Masquerade : a Blue Bloods novel - De la Cruz, Melissa, 1971- (New York : Hyperion, 2007)
Schuyler Van Alen, growing comfortable with her newfound vampire powers, seeks her grandfather in Italy, while back in New York plans are being completed for the fabulous Four Hundred Ball, to be followed by an elite, teens-only event at which masks hide a terrible secret
Keywords: Vampires -- Fiction; Wealth -- Fiction; Balls (Parties) -- Fiction; Masquerades -- Fiction; Secrets -- Fiction; New York (N.Y.) -- Fiction